Abmash: mashing up legacy Web applications by automated imitation of human actions. (11th December 2013) - Ortac, Alper; Monperrus, Martin; Mezini, Mira
Summary Many business Web‐based applications do not offer APIs to enable other applications to access their data and functions in a programmatic manner. This makes their composition difficult (for instance to synchronize data between two applications). To address this challenge, this paper presents Abmash, an approach to facilitate the integration of such legacy Web applications by automatically imitating human interactions with them. By automatically interacting with the GUI of Web applications, the system supports all forms of integrations including bidirectional interactions and is able to interact with AJAX‐based applications. Furthermore, the integration programs are easy to write because they deal with end‐user, visual UI elements. The integration code is simple enough to be called a 'mash‐up'. Copyright © 2013 John Wiley & Sons, Ltd.